Several Views on the Common History of Medieval Central Asia and East Turkestan - Kaiyrken Т.З. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The article examines the historical and geographical connections of Central Asia and East Turkestan in the Middle Ages. It is known that these two regions have played a special role in the spiritual, cultural and economic relations between the West and the East since ancient times. The ancient Silk Road first crossed this region in the past, and then continued to the east and west. At one time, the geopolitical importance of the region also increased due to the influence of the Silk Road. In the 8th century, this region became an arena for the struggle for influence between the Arab, Tibetan and Tang empires. But ultimately, none of them managed to establish their dominance here. Central Asia and East Turkestan were under a single political authority created by the indigenous Turkic peoples, both in the early Hunnic and Turkic eras, and in the medieval era of the Karakhanid, Kara-Khitan, Chagatai khanates and Moghulstan. Therefore, both geographically and historically, it was an integral part of all of Central Asia or all of Turan. The article focuses on interregional relations during the Karakhanid state. The article examines the foreign policy of the newly formed Karakhanid state in the valleys of the Shu and Talas rivers in the middle of the 9th century, which developed as a result of the interaction of the ancient Uyghur (Oguz) tribes who migrated from Central Mongolia and the local Karluk and Yagma tribes. Then, the historical place of Kashgar as one of the two capitals of the Karakhanid state is emphasized. The history of the development and prosperity of East Turkestan as part of the Karakhanid state, the spread of Islam, and the process of Turkification of the entire Yeti-Shahar are analyzed. This proves that during the era of the Karakhanid state, East Turkestan was part of it. This conclusion radically changes the previously established historiographic views. The article also analyzes the political, economic and ethnic conditions in Central Asia and East Turkestan during the Chagatai Khanate and the Mughal Empire. The struggle for power between the dynasties of Ogedei and Chagatai, as well as the growing influence of the local Dulat nobility in the interior of the khanate contributed to the expansion of the state’s borders to the east and south. As a result, the eastern border of Mogolstan reached the Great Wall of China. And such large possessions as Kashgar, Kotan, Zharkent, Aksu, Kusan became internal regions of the state. Based on these facts, the author proves that East Turkestan was also part of the Chagatai ulus and the Mogul state, which was expanding throughout Central Asia during this period.